Implementing Bugis-Makassar Local Wisdom Within The Prosecutor's Office In Parepare City, South Sulawesi - Pradana, Syafa'at Anugrah; Pikahulan, Rustam Magun; Alvian, Muhammad Andri (Jurnal Dinamika Hukum, 2023)
Public service is essentially part of the government's role in serving and fulfilling the interests of society. However, in practice, the implementation of public services has not been able to meet public expectations or public service standards stipulated in Law No. 25 of 2009, especially the implementation of public services by the Prosecutor's Office. The method used is socio-legal using a sample, namely the Prosecutor's Office in South Sulawesi. The problems that are present in three fundamental aspects that determine the quality of public services in the Prosecutor's Office starting from the pattern of public service delivery, the quality of human resources, and institutions indicate the need for improvements to excellent public services to realize good governance in Indonesia. Therefore, the conclusion that can be drawn is the implementation of the principles of sipakatau, sipakainge, and sipakalebbi in public services in the Prosecutor's Office is a solution to excellent public services.